Synthesis, DFT analysis and DNA studies, cytotoxicity and luminescence properties of a dinuclear copper(II) complex with 1, 10-phenanthroline and 4-aminobenzoate. Issue 5 (3rd April 2019) - Baskaran, S.; Murali Krishnan, M.; Arumugham, M. N.; Kumar, R.
Abstract: The dinuclear copper(II) complex, [Cu2 (phen)2 (4-aminobenzoate)2 (H2 O)2 ](NO3 )2 ·2(4-aminobenzoic acid)·3H2 O (phen = 1, 10-phenanthroline), has been synthesized and structurally characterized by elemental analyses, IR, EPR, UV-visible and single-crystal X-ray crystallography. The complex crystallized in a monoclinic system with space group C2/c, a = 26.0022(10) Å, b = 10.2524(4) Å, c = 20.9983(7) Å, α = 90°, β = 106.9550(10)° and γ = 90°. The Cu(II) ion adopts a distorted square-pyramidal geometry formed by two N atoms from the phen ligand and two O atoms of the two 4-aminobenzoic acid ligands and one water O atom. The Cu…Cu separation is 3.0570(5) Å. A twofold axis passes through the midpoint of the Cu-Cu vector. The complex has intraligand (π–π*) fluorescence properties. The binding of this dinuclear copper(II) complex with calf thymus DNA (CT-DNA) was investigated by UV-vis absorption, fluorescence spectroscopic, cyclic voltammetric and viscosity techniques. Also, the cleavage of pBR322 DNA with dinuclear copper(II) complex was studied using gel electrophoresis method. The exhibited potent cytotoxic effects against human cell line (HepG2) and it was found to have good antimicrobial activities. The primary coordination sphere of dinuclear copper(II) complex is optimized, structural parameters are calculated and energy gaps of frontier orbital (HOMO-LUMO) have been calculated with B3LYP/6-31G/LANL2DZ level of theory in the gaseous phase. The calculated geometric and spectral results reproduced the experimental data with well agreement. Theoretical calculated molecular orbitals (HOMO-LUMO) and their energies have been calculated that suggest charge transfer occurs within the complex. Graphical Abstract: